Tanshinone IIA Promotes M2 Microglia by ERβ/IL-10 Pathway and Attenuates Neuronal Loss in Mouse TBI Model - Chen M (Dove Medical Press, 2020)
Mingrui Chen,1 Qiulin Chen,1 Tao Tao2 1Department of Neurosurgery, Chongqing Red Cross Hospital (People’s Hospital of Jiangbei District), Jiangbei, Chongqing 400020, People’s Republic of China; 2Department of Rehabilitation Medicine, Guizhou Provincial People’s Hospital, Guiyang, Guizhou 550002, People’s Republic of ChinaCorrespondence: Tao Tao Tel +86 13985162824Email 13985162824@163.comPurpose: Traumatic brain injury (TBI) is a major cause of morbidity and mortality worldwide. Increasing evidence indicates that activated microglia play an important role in the inflammatory response in TBI. Inhibiting M1 and stimulating M2 activated microglia have protective effects in several animal models of central nervous system (CNS) disorders. In the present study, we investigated whether tanshinone IIA (TNA) protects neurons by shifting microglia polarization in a mouse TBI model and further investigated the mechanism in vitro.Materials and Methods: Forty C57BL/6 mice were used to investigate the effect of TNA on microglia polarization in TBI. BV-2 cells were used to examine the mechanism of TNA in regulating microglia polarization.Results: Normal saline (NS), TNA and the combination of TNA with ICI 182,780 (ICI, an estrogen receptor antagonist) were used to treat the TBI mice. After TBI, mice from each group demonstrated functional improvement. The improvement rate in mice treated with TNA was faster than other groups. ICI partially reversed the benefits from TNA treatment. TNA treatment significantly reduced TBI-induced neuronal loss. The number of microglia after TBI was not significantly changed by TNA treatment. However, TNA treatment significantly decreased M1 macrophage markers (iNOS, TNFα and IL-1β) and increased M2 macrophage markers (CD206, arginase 1 and Ym1). This effect was partially abolished by ICI. TNA treatment downregulated M1 macrophage markers and upregulated M2 macrophage markers in BV-2 cells under LPS stimulation. IL-10 was significantly increased by TNA treatment without a significantly change of IL-4 and IL-13 expression. IL-10 knockdown completely abolished the effect of TNA on microglial M2 polarization.Conclusion: Taken together, our data demonstrated that TNA attenuates neuronal loss in mouse TBI model and promotes M2 microglia by ERβ/IL-10 pathway. Thus, TNA could be a potential drug for TBI and/or the disorders that caused by microglial over-activation in CNS.Keywords: tanshinone IIA; TNA, traumatic brain injury; TBI, microglia, interleukins, macrophage polarization